A Ground book on engineering mathematics Vol-2 - Mukherjee, Arup Kumar (Shreedhar Prakashani, 2016)
A Ground book on engineering mathematics Vol-2 / Mukherjee, Arup Kumar. -- Kolkata: Shreedhar Prakashani, 2016 510 M941v2 No. of Copies : 1